FIGURATIVE LANGUAGE AND SPEECH ACTS IN "THE ADVENTURES OF SHERLOCK HOLMES": A STUDY ON DESCRIPTIVE TEXTS - Bahing, Bahing; Meilantina, Mayang; Fadhly, Fahrus Zaman (English Review: Journal of English Education, 2024)
Abstract This study explores the intricacies of figurative language and speech acts within five selected short stories from "The Adventures of Sherlock Holmes." Through a qualitative analysis grounded in the theories of Austin and Searle for speech acts, and further supported by the descriptive insights of figurative language as discussed by Adiwangsa & Sakinah (2023) and Ampa & Quraisy (2018), this research aims to identify the dominant types of speech acts and the underlying meanings conveyed through figurative expressions. The methodology encompasses content analysis, with the researcher herself acting as the primary instrument, supplemented by digital tools for text examination. The findings reveal the prevalence of directive, expressive, and representative speech acts manifested in similes, metaphors, and metonyms, underscoring the significance of these linguistic features in enhancing the interpretative richness of literary texts. This study contributes to the broader discourse on linguistic analysis in literature, offering insights into the dynamic interplay between language form and function, and its educational implications in English Language and Arts curricula.